2022
DOI: 10.1038/s41598-022-10340-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the process and rate of exogenous DNA degradation during digestion in mice

Abstract: This study aimed to perform qualitative and quantitative examination of DNA degradation during the digestion process in the mouse gut through PCR, qPCR and short tandem repeat (STR) analysis. Human blood leukocytes were gavaged into the digestive tract in mice. GAPDH, TH01, TPOX and D7S820 genes in the contents of the stomach and small intestine were analyzed with PCR and qPCR at various times pre- and post-gavage. Through STR analysis, 21 human genomic DNA loci were analyzed. The half-life of DNA degradation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…When studying the survival of exogenous DNA in the GI tract of mice, a recent study observed an approximate half-life of 71 minutes at the gastric phase; 316 we could not find any studies reporting the gastric half-life of exogenous RNA although we estimate it to be lower due to the decreased stability of a single nucleotide strand. 317 It may be assumed however that RNA may be stabilized in various food matrices given protection of plant cells that are not easily broken down during digestion, such as exosome-like nanoparticles of plant origin (ELN).…”
Section: Novel Markers-nucleic Acidscontrasting
confidence: 74%
“…When studying the survival of exogenous DNA in the GI tract of mice, a recent study observed an approximate half-life of 71 minutes at the gastric phase; 316 we could not find any studies reporting the gastric half-life of exogenous RNA although we estimate it to be lower due to the decreased stability of a single nucleotide strand. 317 It may be assumed however that RNA may be stabilized in various food matrices given protection of plant cells that are not easily broken down during digestion, such as exosome-like nanoparticles of plant origin (ELN).…”
Section: Novel Markers-nucleic Acidscontrasting
confidence: 74%
“… 117 In practice, however, it is not feasible to use gastric juice DNA for molecular diagnosis because DNA is easily damaged by stomach acid (strongly acidic, pH less than 3). 118 , 119 Watanabe et al have proposed an alternative to the highly acidic gastric juice for molecular analysis using gastric washes, which is the flushing fluid (gastric mucosa and normal saline) obtained during routine endoscopy. Of the six hypermethylated genes ( RORA , ADAM23 , MLF1 , MINT25 , GDNF , and PRDM5 ), GDNF and MINT25 are the most sensitive biomarkers for early GC, and in terms of gastric washes, the MINT25 site has the best specificity (95.8%) and sensitivity (90%).…”
Section: Dna Methylation Ignites a Revolution In The Early Detection ...mentioning
confidence: 99%
“…Additionally, ingested dietary DNA and DNA fragments are partially degraded through the GIT by acids, enzymes, and microbial activities ( Zhu et al, 2004 ; Wiedemann et al, 2006 ). A recent study showed that approximately 86% of the exogenous DNA degraded in the stomach of mice 2 h after oral gavage and almost complete degradation was observed within 40 min after entering the small intestine ( Xing et al, 2022 ). Besides, the probability of detection of the short fragments in the GIT is higher in avian species due to the fast passage rate of the feed compared to mammals ( Klotz et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%